2019
DOI: 10.1016/j.csbj.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on the Molecular Mechanism of Cervical Carcinogenesis Based on Systems Biology Technologies

Abstract: Cervical cancer is one of the common malignancies in women worldwide. Exploration of pathogenesis and molecular mechanism of cervical cancer is pivotal for development of effective treatment for this disease. Recently, systems biology approaches based on high-throughput technologies have been carried out to investigate the expression of some genes and proteins in genomics, transcriptomics, proteomics, and metabonomics of cervical cancer. Compared with traditional methods,systems biology technology has been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 146 publications
0
29
0
11
Order By: Relevance
“…Cervical cancer is one of the leading causes of death among women worldwide [ 1 ], currently ranking as the fourth most prevalent cause of cancer death [ 2 ]. Cervical cancer is associated with a poor prognosis due to the characteristic invasion and metastasis and thus requires more efficient therapeutic targets for the treatment [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer is one of the leading causes of death among women worldwide [ 1 ], currently ranking as the fourth most prevalent cause of cancer death [ 2 ]. Cervical cancer is associated with a poor prognosis due to the characteristic invasion and metastasis and thus requires more efficient therapeutic targets for the treatment [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, the occurrence and development of CC is hypothesized to be linked with persistent HPV infection (100); however, the specific molecular mechanisms require further investigation. In addition, although a number of studies are examining the molecular mechanisms of CC (101)(102)(103)(104), the detailed pathological process remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although earlier studies have reported on progress in elucidating the potential molecular mechanism of CC development [ 22 , 23 ], the fundamental knowledge of this mechanism remains problematic. As HPVs are DNA viruses with epithelial tropisms, HPV infection results in activation of the DNA damage repair mechanism [ 13 ].…”
Section: Discussionmentioning
confidence: 99%